Pengaruh Model Project Based Learning (PjBL) terhadap Kemampuan Berpikir Kritis dan Hasil Belajar Siswa pada Materi Sel - Nur Istikhomah; Masitah Masitah; Zenia Lutfi Kurniawati; Vandalita M. M. Rambitan; Jailani Jailani; Akhmad Akhmad (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
The low critical thinking skills and student learning outcomes in science learning are still the main problems in schools. This study aims to determine the influence of the Project Based Learning (PjBL) learning model on the learning outcomes and critical thinking skills of grade VIII students on animal cell and plant cell materials at SMP Muhammadiyah 6 Samarinda. This study uses a quantitative method with a quasy experimental nonequivalent control group design. The sample totaled 50 students consisting of 25 students in the experimental class and 25 students in the control class. The research instrument is in the form of an essay test consisting of 10 questions. The results showed that the average post-test learning outcomes of the experimental class were higher (82.6) than the control class (59.2). In critical thinking skills, the experimental class obtained an average of 81.8 with the very good category, while the control class obtained 50.5 with the fair category. The results of the t-test showed a significant difference between the two classes (sig. < 0.05). Thus, the application of the Project Based Learning (PjBL) learning model can be recommended to improve critical thinking skills in science learning in junior high school.